2019
DOI: 10.1002/adma.201805417
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering of 2D Materials: Issues and Opportunities at the Interface

Abstract: applications of 2D materials emerging at large strain levels. [8][9][10] Considering difficulties associated with building a microelectromechanical system for straining freestanding 2D materials, [11] 2D materials were often transferred onto a substrate such that the strain can be introduced to the 2D material by controlling the deformation of the bulk substrate. [12] Such fact has led to significant advances in the strategies for straining 2D materials with a film-substrate system, as well as in interface met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
348
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(382 citation statements)
references
References 162 publications
3
348
0
2
Order By: Relevance
“…Mechanic strain is an effective way to alter the electronic and optical properties by deforming the crystal lattice . Recently, strain has been proved as an effective method to engineer the NLO .…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
“…Mechanic strain is an effective way to alter the electronic and optical properties by deforming the crystal lattice . Recently, strain has been proved as an effective method to engineer the NLO .…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
“…Our results suggest that using low‐Schottky barrier contacts or 2D support materials whose Fermi level is closely aligned with 2D semiconducting catalysts are promising strategies for reducing E B . Recent advances in strain engineering of 2D TMDs have shown that their electronic band structure is sensitive to strain, and could be used to tune the contact resistance at semiconductor–metal interfaces. Some work has demonstrated that strain engineering can also be used to improve the HER activity of TMDs by modifying Δ G H .…”
Section: Resultsmentioning
confidence: 99%
“…Experimental investigations have shown tunable physical properties for optoelectronic applications can be achieved by using strain engineering. [54] In particular, the in-plane epitaxial strain utilized in the 2D semiconductor even produce novel electronic structures. [36] We studied the evolution of the electronic structures as a function of uniaxial strain ε x(y) along the the x (y)axis.…”
Section: The Influence Of Uniaxial Strain On Electronic Propertiesmentioning
confidence: 99%